Angel Investing Trends and Characteristics in the EU - Đekić, Marija; Vesić, Tamara; Stanković, Miloš (<center>Conference Proceedings Determinants Of Regional Development</center>; No 3 (2022): Conference Proceedings - IX International Scientific Conference Determinants of Regional DevelopmentDO - 10.14595/CP/03/004, 2022)
The financing of entrepreneurial ventures in the European Union is facing many challenges, but its actors are constantly striving to improve its market conditions in order to provide support to entrepreneurs in the early stages of development. Business angel investments, as the most common source of financing in the early stages of enterprise development in the European Union, have been recognized as a form of investment that transcends national borders. The growth of business angel investments has been slowed down by the global pandemic, but there is no doubt that this form of investment is growing, and business angels have long not been just individuals who invest only in the early stages of enterprise development, so by uniting these individuals, there are created new investment concepts that expand their activities into later stages of company development. In 2020, business angel investments accounted for the largest share of the European investment market, or about 58% of the total investment market in the early stages of enterprise development. In 2020 alone, these investments amounted to as much as 7.67 billion euros, and in 2019 to as much as 8.04 billion euros. Disorders in the economy caused by the pandemic will undoubtedly affect all segments of the European economy, but the survival and development of small businesses are part of the economic recovery after the crisis, so all hope lies in that investments of business angels and other forms of early business financing will continue to grow. It’s not odd that such investors are currently looking for companies to finance outside domestic economies, because geographical distance in the conditions of a high degree of globalization is becoming less and less important. However, cross-border investments remain a challenge.